Religion, Animals, and Racialization: Articulating Islamophobia through Animal Ethics in The Netherlands - Mariska Jung (Religions, 2022)
In 2008, the Dutch Party for the Animals submitted a proposal to ban religious slaughter without prior stunning. The proposal was widely supported in the Lower House but finally rejected in the Upper House in 2012, mainly on the grounds of religious freedom. Academia was keen to study the polemic, but no research has attempted to study the controversy through a lens of racialization. This is remarkable, given the well-documented increase in Islamophobia and the political use of racism since (at least) the turn of the millennium in The Netherlands (and the geopolitical “West” at large). In this article, I demonstrate that a racializing dynamic is actually part and parcel of the Dutch controversy. I apply a reflexive thematic analysis to study archival material from the Dutch Parliamentarian debate and show that the dispute foremost references Islamic slaughter. Appeals to civilization, accusations of barbarism, dystopian warnings against Islamization, and invocations of Judeo-Christianity are discursive elements that feature in the debate and have racializing ramifications for Muslims. By unmasking this racializing dynamic, I offer a means to empirically explore the ways in which taxonomies of religion and race intersect with and through the politicization of animal ethics. When considering religious slaughter it is essential, I ultimately maintain, to observe the violence caused by socially constructed racial and species differences. Only if we hold both in serious regard do we have a chance to begin to imagine ourselves in relation to others differently and move towards more just futures—for humans and non-humans alike.